Relying on the Ground Game: The Placement and Effect of Campaign Field Offices. (May 2014) - Darr, Joshua P.; Levendusky, Matthew S.
Though elite-based campaign mobilization was thought to be dead just a few election cycles ago, it has come roaring back in recent years. The vast majority of this direct voter outreach is coordinated through campaign field offices. Despite the increasing importance of such activities, little is known about where campaigns choose to locate these field offices and what effect campaign offices have on election outcomes. We develop a theoretical argument about where candidates will locate these offices, and test our argument using data from recent elections. We also show that these field offices increase county-level vote share by approximately 1%, netting Obama approximately 275, 000 additional votes in the 2008 election. We conclude by discussing the normative implications of increased campaign investment in field operations.